2018
DOI: 10.1093/imrn/rny104
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Limit Theorem for the Sine-Process

Abstract: The main result of this paper is a functional limit theorem for the sine-process. In particular, we study the limit distribution, in the space of trajectories, for the number of particles in a growing interval. The sine-process has the Kolmogorov property and satisfies the Central Limit Theorem, but our functional limit theorem is very different from the Donsker Invariance Principle. We show that the time integral of our process can be approximated by the sum of a linear Gaussian process and independent Gaussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It is shown that the time integral of the sinusoidal process can be approximated as a sum of a linear Gaussian process and independent Gaussian fluctuations. It is proved that the two types of linear statistics are variance-growing and variance-bounded [12]. Scholars such as Magdziarz, M and others propose an alternative definition of ctrw with continuous trajectories and give a scalar limit theorem for this random walk sequence.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the time integral of the sinusoidal process can be approximated as a sum of a linear Gaussian process and independent Gaussian fluctuations. It is proved that the two types of linear statistics are variance-growing and variance-bounded [12]. Scholars such as Magdziarz, M and others propose an alternative definition of ctrw with continuous trajectories and give a scalar limit theorem for this random walk sequence.…”
Section: Introductionmentioning
confidence: 99%